Social cytopathology: Building a stronger cytopathology community through social media. Issue 12 (26th October 2017) - Fuller, Maren Y.; Gardner, Jerad M.; Jiang, Xiaoyin Sara
Abstract : Social media use can enhance education, networking, and collaboration in cytopathology. It can increase the impact of cytopathologists and elevate the understanding of cytopathology specifically and pathology in general among patients, colleagues, and the general public.